Revising and devising a classification scheme for Islam : the IIUM Library's experience - Mukhtar, Noraini; Mohd Daud, Rasyidah Mohd Daud; Musa, Mohamad Ridzuan Musa; Ramli, Latifah; Rabingan, Siti Aidah Rabingan (2016)
The current locally expanded LCC scheme of subclass BP (Islam) used by the IIUM Library, can no longer accomodate the emerging new and sophisticated topics on Islam and Islamic perpectives. IIUM Library decided to revise and devise a new classification scheme for Islam that can blend the would-be classified collection using the new scheme, naturally into the existing collection arrangement. This paper relates the library’s experience, highlighting the important issues that arises from the exercise. It can be a note sharing exercise with other libraries having similar intention or plans, either to expand the existing classification or devise a new classification scheme on Islam altogether.